ลีลาภาษาของเกตุเสพย์สวัสดิ์ ปาลกะวงศ์ ณ อยุธยา (น้าเน็ก) ในรายการอย่าหาว่าน้าสอน : Language Style of Ket-Saepsawad Palakawong Na Ayutthaya (Na-Nek) On the “Ya Ha Wa Na Son” Channel - ลีสีคำ, อานนท์; จันทร์เทาว์, รัตนา (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2020)
This research is in the Thai language subject, and it is qualitative research. The aim is to analyze the language style of Kathsepsawad Palakawong na Ayuthaya (Na Nek). The data was collected in the Ya-Ha Wa Na Son programme published on Youtube Channel in 2020. There are 50 VDO clips. The conceptual framework of language style is a research framework. The research finding was shown that the prominent language style has 4 characteristics that are: 1) word and using; pronoun, slang, colloquial word, dignity word, new word construction, English using, and reduplication. 2) Using the sentence, the finding showed that he often uses for reminding explanatory, commenting, commanding or request, and contradiction. 3) Using figurative, there are frequently 5 types used: metaphor, simile, declaration, hyperbole, and personification. 4) The non-verbal language, in addition, is Na-Nek style such as dressing style, scene, vocalic, and movement. This finding shows that the verbal and non-verbal style of Na-Nek is an informal style to make intimacy with his listeners on the program, which is to affect the popularity of his viewers.